Apolipoprotein epsilon4 allele frequency in young Africans of Ugandan descent versus African Americans. - Willis, Floyd (National Medical Association, 2003)
Through its role in lipid metabolism, Apolipoprotein epsilon4 (ApoE4) may affect "brain repair" in stroke, brain hemorrhage, Alzheimer's disease, and other brain injury syndromes for which African Americans may have greater morbidity and mortality. Cross-cultural evaluations of these and other genetic factors may provide insight on possible ethnic differences in risk of morbidity to acute central nervous system (CNS) injury and chronic neurodegenerative processes. As an initial step toward expanding knowledge of ApoE allele frequencies for persons of African descent, we compared ApoE genotype of a group of 70 young Ugandans to 59 (subset of a larger group of 342 African Americans of all ages) age-matched African Americans and to published frequencies for Caucasians and Asians. We found that the ApoE4 and epsilon2 alleles are more frequent in Ugandans (U) than Caucasians (C) or Asians (A) with corresponding alleles showing significant elevations of epsilon2 (U 15.71%, C 8.40%, A 4.20%) and 14 (U 25%, C 13.70%, A 8.90%) (p < .001). Comparing the differences between Ugandans and age-appropriate African Americans (AA) was not statically significant, but this outcome may be due to small sample size. These results provide the only published ApoE frequencies for Ugandans and the complete set of data provides the largest published community group of ApoE frequencies for African Americans.